Adsorption of toluene‐3, 4‐dithiol on silver islands investigated by surface‐enhanced Raman spectroscopy. (13th February 2020) - Plaickner, Julian; Speiser, Eugen; Chandola, Sandhya; Esser, Norbert; Singh, Dheeraj K.
Abstract: The adsorbtion of toluene‐3, 4‐dithiol (TDT) molecules on Ag islands was investigated with surface‐enhanced Raman spectroscopy (SERS). The SERS spectrum was compared with the ordinary Raman spectrum of TDT, and differences in spectral features were discussed with the support of density functional theory calculations. The disappearance of all the S–H‐related bands in the SERS spectrum indicates that TDT adsorbs on Ag via both thiol groups, as supported by the emergence of a weak band at 223 cm −1 attributed to Ag–S stretching. Signatures of Ag–S–C complexes suggest that the adsorption is partially disordered. The observation of all the vibrational modes involving the methyl group indicates that the methyl group is exposed, offering new functionalization possibilities of the surface. Abstract : Adsorption of Toluene‐3, 4‐dithiol(TDT) molecules on Ag islands in ultra‐high vacuum (UHV) was investigated with Surface‐enhanced Raman spectroscopy. Ab‐initio calculations allowed for a detailed assignment of vibrational modes. The results indicate that TDT adsorbson Ag via both thiol groups and with the methyl group exposed. This configuration is suitable for further surface functionalization. Because of the excluded multilayer formation, S‐S stretching vibrations were attributed to apartial dimerization of the molecules.